Nucleation Behavior of SnS2 on Thiol Functionalized SAMs During Solution-Based Atomic Layer Deposition - Götz, Klaus; Prihoda, Annemarie; Shen, Chen; Dierner, Martin; Dallmann, Johannes; Prusch, Saskia; Zahn, Dirk; Spiecker, Erdmann; Unruh, Tobias (Advanced Materials Interfaces, 2024)
Solution-based atomic layer deposition (sALD) is an emerging technique that transfers the principle of traditional atomic layer deposition (ALD) from the gas phase into a wet chemical environment. This new preparation technique has new and unique properties and requirements. A large number of new surfaces and reactants are available to produce active 2D materials. In this work a reproducible procedure to coat silicon wafers with a densely packed monolayer of (3-Mercaptopropyl)trimethoxysilane (MPTMS) molecules is presented. These highly functionalized surfaces can be used to seed the nucleation of SnS2 in a solution-based ALD procedure. A coating routine for the production of SnS2 is adapted from ALD to sALD and insight into the nucleation behavior of the reactands is given. X-ray reflectometry (XRR) is used to resolve the nucleation process of SnS2 on an MPTMS self assembled monolayer (SAM) during the first three cycles of an sALD procedure. The comparison of ex situ XRR, in situ XRR, grazing incidence wide-angle X-ray scattering (GIWAXS), atomic force microscopy (AFM), energy dispersive X-ray spectroscopy (EDX) measurements, and density functional theory (DFT) calculations find that SnS2 first forms a closed layer and then continues to grow in islands on thiol functionalized silane SAMs. Subsequent coating cycles will continue the growth of the islands laterally and in height.
CRIS-Team Scopus Importer:2024-08-09
Keywords: AFM; GIWAXS; sALD; SAM; solution atomic layer deposition; XRR